Urban land cover classification from high resolution Geoeye-1 imagery using a lidarbased digital surface model - Etoughe Kongo, Ulrich Pavlique (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.